2022
DOI: 10.1038/s41598-022-04961-1
|View full text |Cite
|
Sign up to set email alerts
|

Gradual exposure to Coriolis force induces sensorimotor adaptation with no change in peripersonal space

Abstract: The space immediately surrounding the body is crucial for the organization of voluntary motor actions and seems to be functionally represented in the brain according to motor capacities. However, despite extensive research, little is known about how the representation of peripersonal space is adjusted to new action capacities. Abrupt exposure to a new force field has been shown to cause the representation of peripersonal space to shrink, possibly reflecting a conservative spatial strategy triggered by consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Some pioneer studies of Paillard (see Clarac et al, 2009 for a review) reported possible interactions between two levels of action control: the sensorimotor level, which interacts directly with the environment through motor commands and ultimately movement, and the cognitive level, integrating sensory inputs to constantly update internal representations and reference frames. While these two levels communicate and can be influenced by each other, some degree of independence is maintained, allowing one-sided updates and different levels of shared information to external sensory stimulation ( Leclere et al, 2022 ). Our findings supported that claim, in that spatial information processing was rapidly influenced by coherent visual exposure with respect to the locomotor activity being performed, despite the visual condition having no consequence on the observed neuro-mechanical adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Some pioneer studies of Paillard (see Clarac et al, 2009 for a review) reported possible interactions between two levels of action control: the sensorimotor level, which interacts directly with the environment through motor commands and ultimately movement, and the cognitive level, integrating sensory inputs to constantly update internal representations and reference frames. While these two levels communicate and can be influenced by each other, some degree of independence is maintained, allowing one-sided updates and different levels of shared information to external sensory stimulation ( Leclere et al, 2022 ). Our findings supported that claim, in that spatial information processing was rapidly influenced by coherent visual exposure with respect to the locomotor activity being performed, despite the visual condition having no consequence on the observed neuro-mechanical adjustments.…”
Section: Discussionmentioning
confidence: 99%